People to be loved : why homosexuality is not just an issue - Sprinkle, Preston M., 1976- (Grand Rapids, Michigan : Zondervan, 2015)
Christians who are confused by the homosexuality debate raging in the US are looking for resources that are based solidly on a deep study of what Scripture says about the issue. In People to Be Loved, Preston Sprinkle challenges those on all sides of the debate to consider what the Bible says and how we should approach the topic of homosexuality in light of it. In a manner that appeals to a scholarly and lay-audience alike, Preston takes on difficult questions such as how should the church treat people struggling with same-sex attraction? Is same-sex attraction a product of biological or societal factors or both? How should the church think about larger cultural issues, such as gay marriage, gay pride, and whether intolerance over LGBT amounts to racism? How (or if) Christians should do business with LGBT persons and supportive companies? Simply saying that the Bible condemns homosexuality is not accurate, nor is it enough to end the debate. Those holding a traditional view still struggle to reconcile the Bible's prohibition of same-sex attraction with the message of radical, unconditional grace. This book meets that need. - Amazon
"My name was faggot" -- Holy otherness : is male and female sexual difference necessary for marriage? -- From sex in the city to law & order : homosexuality in the Old Testament -- Rated R : homosexuality in Judaism and Greco-Roman culture -- Whom would Jesus love? Homosexuality adn the savior -- Fall short of God's glory : homosexual and heterosexual sins in Romans ! -- Lost in translation : homosexuality in 1 Corinthians 6:9 and 1 Timothy 1:10 -- Interlude : a summary -- "Born this way" : does God make people gay? -- Gay and Christian : can someone be both? -- On the side of the angels : what does Christian faithfulness look like?.
Includes bibliographical references.
Keywords: Homosexuality -- Biblical teaching; Homosexuality -- Religious aspects -- Christianity